An essay on loan forbearance - Mourad, Frederico Abou (2019)
Forbearance is a concession granted by a lending bank to a borrower for reasons of financial difficulty. This thesis examines why and when delinquent bank loans are forborne, using a novel dataset with over 13 million delinquent loans to non-financial firms in Brazil, from which 1.1 million are forborne. My evidence shows that larger loans are more likely to be forborne, and more than 80% of forbearance events occur in less than four months after a loan becomes more than 60 days past due (after which the bank may no longer accrue interest). I also show that the greater the difficulty to seize collateral, the largest the probability of forbearance. Previous forbearances to a borrower are also positively associated to the probability of forbearance, which may be an indicative of loan evergreening. I also find that a regulatory rule that forces banks to increase provisions of non-delinquent loans when the same borrower also has a delinquent loan creates incentives for banks to forbear delinquent loans. Finally, using productivity data of more than six thousand state judicial courts in Brazil, I find a weak evidence that court congestion may affect the decision of forbearance. Because loan evergreening may pose macroeconomic resource allocation problems and forbearance may be used to conceal loan losses, decrease provisions and manage earnings and capital, my findings have implications for the design of regulation and supervisory processes.